Pertemuan Antara Pedagogi Kristen Dan Fikrah Islamiyyah: Menuju Pendidikan Agama Yang Inklusif - Urbanus Sukri (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
This article examines the intersection between Christian pedagogy and fikrah Islamiyyah as a conceptual foundation for developing inclusive religious education within a pluralistic society. This study is motivated by the increasing challenges of intolerance, exclusivism, and religion-based social polarization, which indicate that religious education has not yet fully succeeded in fostering a culture of dialogue and respect for diversity. This research employs a qualitative approach using a literature study method and a conceptual-comparative analysis of various relevant academic sources on Christian pedagogy, Islamic education, multicultural education, and interfaith dialogue. The findings reveal that Christian pedagogy and fikrah Islamiyyah share common ground in values such as love, compassion (rahmah), justice, respect for human dignity, and a humanistic as well as transformative orientation in education. Both paradigms view education as a holistic process of human development, encompassing spiritual, moral, intellectual, and social dimensions. The study also finds that inclusive religious education requires curriculum reconstruction, dialogical pedagogical approaches, and the strengthening of students’ interreligious competencies. Therefore, the integration of values from Christian pedagogy and fikrah Islamiyyah can serve as an important foundation for developing religious education that is tolerant, peaceful, and contextually relevant in contemporary multicultural societies.